IMPROVING STUDENTS' MASTERY OF SIMPLE PRESENT TENSE THROUGH WORDWALL WEBSITE - Khairunnisa, Divia; Astriyanti, Diah; Shinta Sari, Dian (Journal of English Language Teaching and Education (JELTE), 2024)
This research aimed to find out how wordwall website can improve students' mastery of the simple present tense in the tenth grade of SMK Islam Insan Cendekia Mempawah. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, acting, observing, and reflecting phases. The research subjects were 10 students from Software Engineering class. Data were collected through observation, field notes, and tests, and analyzed using both qualitative and quantitative methods. The findings revealed that the use of the Wordwall website significantly enhanced students' understanding and application of the simple present tense. Students' mean scores improved from 62.9 in Cycle 1 to 82.5 in Cycle 2. Additionally, the interactive activities provided by Wordwall, such as Unjumble, Complete the Sentences, and Gameshow Quiz, increased students' engagement and participation in the learning process. The classroom atmosphere also became more conducive to active learning, with reduced distractions and greater student focus. The research concluded that the Wordwall website is improving students' mastery of the simple present tense. It is recommended for educators to incorporate Wordwall website into their teaching strategies to enhance student motivation and learning outcomes. Future researchers are encouraged to explore the application of Wordwall website in other aspects of language learning. Keywords: Wordwall Website, Simple Present Tense, Classroom Action Research.